An integrated model platform for the economic assessment of agricultural policies in the European Union - Ignacio Peŕez Domińguez; Stephan Hubertus Gay; Robert M'Barek (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2008)
A number of economic models have been applied to analyse the Common Agricultural Policy. The partial equilibrium models CAPRI, ESIM, AGLINK, AGMEMOD and CAPSIM and the general equilibrium models GLOBE and GTAP are currently integrated in a modelling platform for Agro-Economic Policy Analysis in the premises of the Joint Research Centre in Seville in close collaboration with Directorate-General for Agriculture and Rural Development. Each of the models included has a specific focus, enlarging the capacity for complex policy analysis within this platform. This can be done by comparing the results of different models or by linking them, where several methodological options are available. This paper gives some insights on current applications in the field of model integration for agricultural policy analysis.
Keywords: 330; EU-Agrarpolitik; Wirkungsanalyse; Wirtschaftsmodell; Forschungskooperation; EU-Staaten